Recent progress in creating complex and multiplexed surface-grafted macromolecular architectures. Issue 38 (24th September 2020) - Xie, Zhuang; Gan, Tiansheng; Fang, Lvye; Zhou, Xuechang
Abstract : Fabrication approaches to complex and multiplexed architectures with surface-grafted macromolecular build blocks are summarized. Abstract : Surface-grafted macromolecules, including polymers, DNA, peptides, etc., are versatile modifications to tailor the interfacial functions in a wide range of fields. In this review, we aim to provide an overview of the most recent progress in engineering surface-grafted chains for the creation of complex and multiplexed surface architectures over micro- to macro-scopic areas. A brief introduction to surface grafting is given first. Then the fabrication of complex surface architectures is summarized with a focus on controlled chain conformations, grafting densities and three-dimensional structures. Furthermore, recent advances are highlighted for the generation of multiplexed arrays with designed chemical composition in both horizontal and vertical dimensions. The applications of such complicated macromolecular architectures are then briefly discussed. Finally, some perspective outlooks for future studies and challenges are suggested. We hope that this review will be helpful to those just entering this field and those in the field requiring quick access to useful reference information about the progress in the properties, processing, performance, and applications of functional surface-grafted architectures.